2008
DOI: 10.4314/ajtcam.v4i2.31207
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants Useful For Malaria Therapy In Okeigbo, Ondo State, Southwest Nigeria

Abstract: There is increasing resistance of malaria parasites to chloroquine, the cheapest and commonly used drug for malaria in Nigeria. Artemisin, a product from medicinal plant indigenous to China, based on active principle of Artemisia annua, has been introduced into the Nigerian market. However not much has been done to project antimalaria properties of indigenous medicinal plants. This study thus, has the main objective of presenting medicinal plants used for malaria therapy in Okeigbo, Ondo State, South west Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(173 citation statements)
references
References 7 publications
9
161
0
3
Order By: Relevance
“…These species were also used in the treatment of malaria as reported in other parts of Ghana [76,77,95]. Azadirachta indica is used in other countries such as Uganda [96], Nigeria [97], and Kenya [98] for the treatment of malaria. Similarly, Tectona grandis (FL = 100%) is utilised in other parts of Ghana [77,99], Nigeria [100], and Cote d'Ivoire [101] for the treatment of malaria.…”
Section: Comparison Of Documented Data On Medicinal Plants With Previmentioning
confidence: 99%
See 1 more Smart Citation
“…These species were also used in the treatment of malaria as reported in other parts of Ghana [76,77,95]. Azadirachta indica is used in other countries such as Uganda [96], Nigeria [97], and Kenya [98] for the treatment of malaria. Similarly, Tectona grandis (FL = 100%) is utilised in other parts of Ghana [77,99], Nigeria [100], and Cote d'Ivoire [101] for the treatment of malaria.…”
Section: Comparison Of Documented Data On Medicinal Plants With Previmentioning
confidence: 99%
“…Vernonia amygdalina (FL = 65%) is highly preferred in Uganda for the treatment of malaria, stomach ache, and convulsions [75] and for managing impotence, dandruff and bloating in Ethiopia [87]. Alstonia boonei is used in treating malaria in Uganda [75], haemorrhoids and malaria in Nigeria [97,104,105]. Senna alata is also utilised in the treatment of skin diseases in Nigeria [106] and Bangladesh [107].…”
Section: Comparison Of Documented Data On Medicinal Plants With Previmentioning
confidence: 99%
“…The leave of Morinda lucida mix together with the bark of Khaya spp are used in the treatment of Malaria are equally reported. This is in tandem with Sofowora, (1993) and Odugbemi et al, 2007 that Morinda lucida and Khaya spp were found to be in use for malaria therapy in Okeigbo area of Ondo-State, Nigeria. The mixtures of other plant species in treating ailments such as Anemia, dysentery and diabetics were also observed as presented in Table 1.…”
Section: Mixtures Of the Plants' Parts With Other Plant Speciesmentioning
confidence: 99%
“…(Burkill, 2000). (Adesokan et al, 2007;Odugbemi et al, 2007). Au Cameroun, l'extrait d'Ă©corce de tige est utilisĂ© pour traiter la jaunisse, les infections des voies urinaires, l'hypoglycĂ©mie, la fièvre typhoĂŻde (FAO, 2001).…”
Section: Introductionunclassified